Are Alum-Based Drinking Water Treatment Residuals Safe for Land Application? - Sampson Agyin-Birikorang; George A. O'Connor; Thomas A. Obreza (EDIS)
SL-299, an 8-page illustrated fact sheet by Sampson Agyin-Birikorang, George A. O’Connor, and Thomas A. Obreza, explores possible effects of land-applying Al-WTR on the environment, and recommends ways to minimize human impacts. Includes further readings. Published by the UF Department of Soil and Water Science, July 2009.